P-34 The development and evaluation of an integrated specialist dementia admiral nurse service within a specialist palliative care community hospice. (19th November 2022) - Bareham, Kerry; Rose, Tom
Abstract : Background: The benefits of a collaborative approach between dementia and hospice services are becoming more clearly realised, with several hospice-based partnerships with Dementia UK to provide specialist Admiral Nurses in palliative services. The Lincolnshire Admiral Nurse Service was commissioned in June 2019 to introduce specialist nursing support and leadership for families living with dementia in Lincolnshire. This was an innovative collaboration between St Barnabas Hospice, Lincolnshire County Council and Dementia UK. During its two years' proof of concept phase, the service demonstrated a positive impact on the lives of carers. It established a valuable and much-needed resource within Lincolnshire for people with complex palliative needs not provided by any other service. Evaluation: Articulating case complexity is not straightforward and using any single category is inadequate for a definition. It is inextricably linked with multiple characteristics, such as health, socioeconomic status, poverty, or accessibility. Managing complexity in healthcare requires the input of specialists with knowledge and expertise across the pathway to directly support those affected and support broader system efforts to meet the needs of the whole population. By providing specialist Admiral Nurses, St Barnabas has supported the delivery of effective and targeted support for families impacted by dementia. Through case studies and logic models, the service evaluation also demonstrated that these needs can only be met by investment in a specialist nursing workforce. A hospice-based service enables a key aim of increasing access to palliative care for those with dementia and supports the synergy of both palliative and dementia care ethos by placing the person at the centre of their care and decision making, and increasing understanding that dementia is a palliative condition. Furthermore, having community-based Admiral Nurses within a hospice enables specialist support for those affected by dementia throughout the entire pathway.